Thrombus-Targeting Polymeric Nanocarriers and Their Biomedical Applications in Thrombolytic Therapy - Guan, Qixiao; Dou, Hongjing (Frontiers in Physiology, 2021)
Due to the high morbidity and mortality of cardiovascular diseases, there is an urgent need for research on antithrombotic strategies. In view of the short half-life, insufficient drug penetration, poor targeting capabilities, and hemorrhagic side-effects of traditional thrombus treatment methods, the combination of thrombolytic therapy and nanocarriers brought by the development of nanotechnology in recent years may provide effective solutions for these undesirable side-effects caused by insufficient targeting. Polymeric nanocarriers, based on macromolecules and various functional groups, can connect specific targeting molecules together through chemical modification to achieve the protection and targeted delivery of thrombolytic drugs. However, simple chemical molecular modifications may be easily affected by the physiological environment encountered in the circulatory system. Therefore, the modification of nanocarriers with cell membranes can provide camouflage to these platforms and help to extend their circulation time while also imparting them with the biological functions of cell membranes, thus providing them with precise targeting capabilities, among which the most important is the biological modification of platelet membranes. In addition, some nanoparticles with their own therapeutic functions have also been developed, such as polypyrrole, which can exhibit a photothermal effect to induce thrombolysis. Herein, combined with the mechanism of thrombosis and thrombolysis, we outline the recent advances achieved with thrombus-targeting nanocarriers with regard to thrombosis treatment. On this basis, the design considerations, advantages and challenges of these thrombolytic therapies in clinical transformation are discussed.